Synthesis of Marine Natural Products and Molecules Inspired by Marine Substances II - Manzo, Emiliano (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This Special Issue, comprising five articles, describes the synthetic methodologies and biological activity of different classes of bioactive marine metabolites and analogs crucial to favor pharmacological applications of these molecules.